2014
DOI: 10.4269/ajtmh.13-0492
|View full text |Cite
|
Sign up to set email alerts
|

Infection Dynamics of Sylvatic Dengue Virus in a Natural Primate Host, the African Green Monkey

Abstract: Abstract. The four serotypes of mosquito-borne dengue virus (DENV-1, -2, -3, and -4) that circulate in humans each emerged from an enzootic, sylvatic cycle in non-human primates. Herein, we present the first study of sylvatic DENV infection dynamics in a primate. Three African green monkeys were inoculated with 10 5 plaque-forming units (pfu) DENV-2 strain PM33974 from the sylvatic cycle, and one African green monkey was inoculated with 10 5 pfu DENV-2 strain New Guinea C from the human cycle. All four monkeys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
1
17
0
1
Order By: Relevance
“…Interestingly, serum ALT levels rose in 2 primates (13367 and 13422) reaching levels close to the upper normal range, which may have been influenced by the high pre-infection levels ( Figure 4 d). Others have shown that serum ALT is elevated following ZIKV infection [ 63 , 64 , 66 , 71 ], in both rhesus and cynomolgus macaques as well as following DENV-2 infections in African green monkeys ( Chlorocebus aethiops ) [ 84 ]. Human disease does not necessarily present with elevated ALT levels but can in cases be associated with hepatic disease and coagulopathy [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, serum ALT levels rose in 2 primates (13367 and 13422) reaching levels close to the upper normal range, which may have been influenced by the high pre-infection levels ( Figure 4 d). Others have shown that serum ALT is elevated following ZIKV infection [ 63 , 64 , 66 , 71 ], in both rhesus and cynomolgus macaques as well as following DENV-2 infections in African green monkeys ( Chlorocebus aethiops ) [ 84 ]. Human disease does not necessarily present with elevated ALT levels but can in cases be associated with hepatic disease and coagulopathy [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…However Vero cells and in vitro techniques are widely available and are useful for preliminary phenotypic experiments prior to investigations in non-human primates (NHPs). In the first study to investigate sylvatic DENV infection in NHPs, researchers have used a small number of African green monkeys to demonstrate that the viremia produced by infection with an African sylvatic DENV-2 strain was of similar magnitude and shorter in duration than the viremia produced by infection with a human endemic DENV-2 strain 44 . With the recent surge in human disease incidence and impending availability of a DENV vaccine, the ongoing study of sylvatic DENV transmission and replication provides a significant contribution to the understanding of DENV prevalence and pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Dengue virus transmission is maintained in urban settings where humans and mosquitoes are the only known hosts, with a sylvatic cycle occurring in non-human primates in forested areas and rarely resulting in transmission to humans 3134 . Central to the global emergence of dengue virus has been the spread of its Aedes species mosquito vectors, in particular Ae.…”
Section: Methodsmentioning
confidence: 99%